The Effect Of Coretax And Tax Knowledge On Taxpayer Compliance With Taxpayer Awareness As A Moderating Variable - Aisa Corolla; Srikalimah; Moch Wahyudi (LP2M IAIN Palopo, 2026)
Abstract This study aims to analyze the influence of Coretax and tax knowledge on taxpayer compliance with taxpayer awareness as a moderating variable at the Kediri Pratama Tax Office in 2025.This research is a quantitative research. The population in this study are Individual Taxpayers (WPOP) who are actively registered and have an obligation to report Annual Tax Returns at the Kediri Pratama Tax Office in 2025. The number of samples in this study is 100 respondents calculated using the Slovin formula. Data collection was carried out using a questionnaire, while the data analysis technique used Moderated Regression Analysis (MRA) with the help of SPSS software. The results of this study indicate that (1) Coretax has a significant positive effect on taxpayer compliance; (2) tax knowledge does not have a significant effect on taxpayer compliance; (3) taxpayer awareness is not able to moderate (does not strengthen or weaken) the effect of Coretax on taxpayer compliance; (4) taxpayer awareness is not able to moderate the effect of tax knowledge on taxpayer compliance; and (5)Coretax, tax knowledge, and taxpayer awareness simultaneously influence taxpayer compliance. Keywords:Coretax, Taxpayer Compliance, Taxpayer Awareness, Tax Knowledge